Job Satisfaction as a Mediating of ShopeeFood Driver Performance in Semarang - Noor Abthal Muqaffi; Tito Aditya Perdana; Artha Febriana; Masitha Fahmi Wardhani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
In 2024, ShopeeFood recorded a transaction value of IDR 16 trillion in Indonesia, compared to IDR 31.1 trillion for GoFood and IDR 41.8 trillion for GrabFood, indicating the necessity for enhancing driver performance to strengthen service competitiveness. This study aims to analyze the impact of work flexibility, work-life balance, and compensation on the performance of ShopeeFood drivers in Semarang City, with job satisfaction serving as a mediating variable. A quantitative approach was employed, utilizing a sample of 105 drivers selected through purposive sampling, and analyzed using SmartPLS 4. The findings reveal that work flexibility does not have a direct effect on performance; however, it positively influences job satisfaction and mediates performance improvement. Work-life balance exerts a direct positive effect on performance but does not significantly affect job satisfaction. Compensation shows a significant positive impact on both job satisfaction and performance. Furthermore, job satisfaction significantly enhances performance, thereby acting as a mediator in the relationship between work flexibility and compensation with performance. These findings offer practical implications for ShopeeFood management in designing more effective work flexibility and compensation policies to improve drivers' job satisfaction and performance. Academically, this study contributes to the literature on the role of job satisfaction as a mediating variable in enhancing driver performance within the platform-based economy.